Optimization of purse seine fishing gear on skipjack tuna (Katsuwonus pelamis) landed at Kutaraja fishing port - Agustina Imelda; Maulidar Nur; Salmarika Salmarika; Thaib Rizwan (BIO Web of Conferences)
Aceh waters are an area with abundant fishery resources, where Skipjack tuna ( Katsuwonus pelamis) is one of the leading commodities. This study aims to assess the optimization of purse seine fishing gear on skipjack tuna catch at the Kutaraja Fishing Port (Type A). The research was conducted in August 2024 using observation and interview methods to collect primary and secondary data. The results showed that skipjack tuna production fluctuated during the 2019-2023 period, with the highest production of 9,704 tons in 2023 and the lowest of 6,103 tons in 2021. The highest fishing effort reached 2,676 trips in 2022, while the lowest was 2,112 trips in 2021. The catch per unit effort (CPUE) value reached 3.69 tons/trip in 2023, indicating that purse seine gear is able to operate optimally in supporting the increase in skipjack tuna catch. Optimization of purse seine gear significantly contributes to skipjack tuna catch at PPS Kutaraja, although production fluctuations are still affected by environmental challenges. Good and ecosystem-based management is needed to maintain the sustainability of skipjack tuna stocks and meet the needs of fishermen and markets.